INCREASING THE ADDED VALUE OF BROILERS IN LHOKSEUMAWE CITY BY DEVELOPING SUPPLY CHAIN AND FOOD BALANCE MODELS - Umaruddin Usman; Likdanawati Likdanawati; Cut Putri Mellita Sari; Ichsan Ichsan (RADJA PUBLIKA, 2022)
The purpose of this study was to determine the supply chain's path or flow pattern from the production source area to the consumer, as well as the parties involved, design a supply chain model, and build a food balance to determine whether there was a surplus or deficit of broiler meat in Lhokseumawe City. Furthermore, utilizing the Hayami technique, this study assesses the added value and profit for traders selling chicken meat. Documents, questionnaires, and interviews with retailers were used to collect data. The findings revealed that retailers controlled or monopolized the supply chain of broiler meat distribution, while producers were accomplices of several large corporations that controlled or monopolized the commodity of broiled chicken in Aceh Province. North Aceh Regency, Pidie Jaya Regency, and Pidie Regency are all sources of commodities coming from outside of Lhokseumawe City. To solve the problem of broiler meat supply, all competent parties, including the government, the commercial sector, relevant agencies/institutions, researchers, academics, scientists, and specialists, must work together to build a design model for the purebred broiler meat supply chain. Most actors cooperate and support one another to gain additional value and profit. Meanwhile, to make up for the losses, a few dealers sell other poultry products including free-range chicken and duck, as well as collect waste from the birds.